Applying RE-AIM to evaluate two community-based programs designed to improve access to eye care for those at high-risk for glaucoma. (December 2017) - Sapru, Saloni; Berktold, Jennifer; Crews, John E.; Katz, L. Jay; Hark, Lisa; Girkin, Christopher A.; Owsley, Cynthia; Francis, Brittney; Saaddine, Jinan B.
Highlights: RE-AIM evaluation framework used for community-based eye care programs on glaucoma. Quantitative and qualitative data were triangulated to assess RE-AIM dimensions. By targeting high-risk populations in communities, programs detected high rates of glaucoma. Evaluation was unable to assess sustainability of programs due to the short duration. Abstract: Introduction: Glaucoma is a leading cause of vision loss and blindness in the U.S. Risk factors include African American race, older age, family history of glaucoma, and diabetes. This paper describes the evaluation of a mobile eye health and a telemedicine program designed to improve access to eye care among people at high-risk for glaucoma. Methods: The RE-AIM (reach, efficacy, adoption, implementation, and maintenance) evaluation framework was used to harmonize indicators. Both programs provided community-based eye health education and eye services related to glaucoma detection and care. Each program reported data on participants and community partners. An external evaluator conducted site visit interviews with program staff and community partners. Quantitative and qualitative data were integrated and analyzed using the RE-AIM dimensions. Discussion: By targeting high-risk populations and providing comprehensive eye exams, both programs detected a large proportion of new glaucoma-related cases (17–19%) – a much larger proportion than that found in the general population (<2%). The educational intervention increased glaucoma knowledge; evidence that it led people to seek eye care was inconclusive. Conclusions: Evaluation findings from the mobile eye health program and the telemedicine program may provide useful information for wider implementation in public health clinics and in optometrist clinics located in retail outlets.